2003
DOI: 10.1103/physreve.68.021102
|View full text |Cite
|
Sign up to set email alerts
|

Shattering transitions in collision-induced fragmentation

Abstract: We investigate the kinetics of nonlinear collision-induced fragmentation. We obtain the fragment mass distribution analytically by utilizing its travelling wave behavior. The system undergoes a shattering transition in which a finite fraction of the mass is lost to infinitesimal fragments (dust). The nature of the shattering transition depends on the fragmentation process. When the larger of the two colliding fragments splits, the transition is discontinuous and the entire mass is transformed into dust at the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 33 publications
(67 reference statements)
1
48
0
Order By: Relevance
“…Collisions with erosion. In collisions with erosion only a small fraction of a particle mass is chipped off (31,37,38). Here we consider a simplified model of such collisions: It takes place when the relative kinetic energy exceeds the threshold energy E eros , which is smaller than the fragmentation energy E frag .…”
Section: [4]mentioning
confidence: 99%
“…Collisions with erosion. In collisions with erosion only a small fraction of a particle mass is chipped off (31,37,38). Here we consider a simplified model of such collisions: It takes place when the relative kinetic energy exceeds the threshold energy E eros , which is smaller than the fragmentation energy E frag .…”
Section: [4]mentioning
confidence: 99%
“…Above 0.5 mm, the curves had an exponential shape (decay), with an exponential distribution parameter of about 0.75 mm. For shorter lengths, the distributions followed a power-law with exponents close to −1.2 (Krapivsky and Ben-Naim 2003), down to very small fragments of 20 µm and below, thus of the fiber diameter scale. This exponent of -1.2 corresponds to the value 0.6 for the fragmentation parameter p. To get an idea of the significance of p, if one assumes that each fiber meets 3000 grits before fiber liberation, and this means that each single contact between a pulpstone grit and spruce wood cuts fiber in two parts with a probability of 2 × 10 −4 .…”
Section: Resultsmentioning
confidence: 93%
“…This study's result with an exponent of -1.2 for the small fragments differed from the expected exponent -3, which would be characteristic for steady source processes (Ben-Naim and Krapivsky 2000). The exponent -1.2 is peculiar to shattering fragmentation when the smaller of two colliding particles splits (Krapivsky and Ben-Naim 2003). According to the theoretical computations, the only asymptotically relevant parameter would be the feed rate , and these grinding trials revealed a faint correlation of feed rate with fiber length distribution.…”
Section: Resultsmentioning
confidence: 94%
“…We can assume this event as the form of two successive steps: formation of an extremely unstable particle in a coagulation step that swiftly breaks into two or more smaller ones. Therefore, the reaction rate of this is taken to be proportional to the numbers of particle per unit volume of the colliding particles . Nonlinear breakage has significant impact in many engineering processes such as fluidized beds, the bulk distribution of raindrops, comminution systems, and several types of milling process .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the reaction rate of this is taken to be proportional to the numbers of particle per unit volume of the colliding particles. 1 Nonlinear breakage has significant impact in many engineering processes such as fluidized beds, [2][3][4][5] the bulk distribution of raindrops, [6][7][8][9] comminution systems, [10][11][12][13] and several types of milling process. [14][15][16][17] Binary collisional breakage is the specific case of the nonlinear breakage, one where the breaking behavior is influenced through the sole of collisions between two particles.…”
Section: Introductionmentioning
confidence: 99%